Effects of dopamine β‐hydroxylase inhibition in pressure overload‐induced right ventricular failure - Stine Andersen; Julie Sørensen Axelsen; Anders H. Nielsen‐Kudsk; Janne Schwab; Caroline D. Jensen; Steffen Ringgaard; Asger Andersen; Rowan Smal; Aida Llucià‐Valldeperas; Frances Handoko de Man; Bruno Igreja; Nuno Pires (Pulmonary Circulation, 2024)
Abstract Activation of the sympathetic nervous system is observed in pulmonary arterial hypertension patients. This study investigates whether inhibiting the conversion of dopamine into noradrenaline by dopamine β‐hydroxylase (DβH) inhibition with BIA 21‐5337 improved right ventricular (RV) function or remodeling in pressure overload‐induced RV failure. RV failure was induced in male Wistar rats by pulmonary trunk banding (PTB). Two weeks after the procedure, PTB rats were randomized to vehicle (n = 8) or BIA 21‐5337 (n = 11) treatment. An additional PTB group treated with ivabradine (n = 11) was included to control for the potential heart rate‐reducing effects of BIA 21‐5337. A sham group (n = 6) received vehicle treatment. After 5 weeks of treatment, RV function was assessed by echocardiography, magnetic resonance imaging, and invasive pressure–volume measurements before rats were euthanized. RV myocardium was analyzed to evaluate RV remodeling. PTB caused a fourfold increase in RV afterload which led to RV dysfunction, remodeling, and failure. Treatment with BIA 21‐5337 reduced adrenal gland DβH activity and 24‐h urinary noradrenaline levels confirming relevant physiological response to the treatment. At end‐of‐study, there were no differences in RV function or RV remodeling between BIA 21‐5337 and vehicle‐treated rats. In conclusion, treatment with BIA 21‐5337 did not have any beneficial—nor adverse—effects on the development of RV failure after PTB despite reduced adrenal gland DβH activity.